Circular Arc Approximation by Quartic H-Bézier Curve - Hussain, Maria; Ong, W. E.; Nazir, Farah; Hussain, Malik Zawwar (University of the Punjab, 2017)
The quartic H-Bézier curve is used for the approximation of circular arcs. It has five control points and one positive real free parameter. The four control points are carried out by